Representasi Bullying dalam Film Vina: Sebelum 7 Hari (Analisis Semiotika Roland Barthes) - Adnan Aditiyana; Iin Soraya; Sari Ekowati Hadi3 (CV Edujavare Publishing, 2024)
Film is a mass communication medium that has a big influence in conveying entertainment and educational messages. In Indonesia, horror films are very popular because of their ability to combine elements of local culture and cinematic innovation. This research analyzes the representation of bullying in the film